A Review of the Piano-Playing-Based-Training Programs in Hand Rehabilitation - Chen, Yu-Ling (My University)
Piano playing requires controlled fine motor movement. Several studies have applied piano playing for patients in hand rehabilitation for its potential to elicit experience-dependent neuroplasticity after stroke or brain injury. Playing the piano also provides auditory feedback to the movement, so patients automatically know whether they have correctly completed the movement or not, and it’s also rewarding. Furthermore, the pleasure of music making motivates the patients to accomplish the demand associated with the repetition of motor tasks. The purpose of this present study is to review the various piano-playing-based-training programs in the rehabilitation literature, specifically those which promote grip strength and finger dexterity in various populations. This study examines multiple factors including the protocols, length, and frequency of the sessions, the assessment tools, and outcomes. The results of this review reveal that most of the programs involved sequence of independent finger movement of varying levels of difficulty. Participants enjoyed the exercise in the sessions and at home, and their fine motor function improved. This review supports the use of piano playing in hand rehabilitation.
Keywords: Health Studies